Validity and reliability of the Connor-Davidson Resilience Scale (CD-RISC) in competitive sport. (March 2016) - Gonzalez, Stephen P.; Moore, E. Whitney G.; Newton, Maria; Galli, Nick A.
Abstract: Objective: This study replicates and extends the work of Gucciardi, Jackson, Coulter, and Mallett (2011) in relation to the validity of the Connor-Davidson Resilience Scale (CD-RISC; Connor & Davidson, 2003) in sport. Three primary aims were explored: 1) Examine the factor structure and fit of three versions of the CD-RISC: the original 25-item CD-RISC, both as a 25-item five factor scale and as a 25-item unidimensional scale, and the 10-item CD-RISC-10; 2) examine gender invariance of the best fitting version of the CD-RISC; and 3) examine the validity of the best fitting CD-RISC by relating it to affect and performance anxiety in a sample of competitive American distance runners (N = 409). Design: Cross-sectional. Methods: Multiple self-report questionnaires were delivered through an online medium. Results: Using confirmatory factor and item level analyses, the CD-RISC-10-item scale was psychometrically superior to the unidimensional 25-item and the five factor 25-item CD-RISC versions. The CD-RISC-10-item exhibited measurement invariance for gender, with significant configural, strong, and weak analyses. Using structure equation modeling, the CD-RISC-10-item scale moderately and positively correlated with positive affect and was inversely related to negative affect and performance anxiety, establishing convergent and divergent validity. Conclusion: The findings offer some initial psychometric evidence for the use of the CD-RISC-10 in sport performers.